Antenatal glucocorticoid treatment is associated with diurnal cortisol regulation in term-born children. (October 2016) - Edelmann, M.N.; Sandman, C.A.; Glynn, L.M.; Wing, D.A.; Davis, E.P.
Highlights: Antenatal glucocorticoids are given to mothers at risk for preterm delivery. There are no known benefits of glucocorticoid treatment in term-born children. Full term children with glucocorticoid treatment displayed altered HPA axis functioning. Antenatal glucocorticoids were associated with lack of a CAR and a flattened diurnal slope. Abstract: Due to the rapid developmental changes that occur during the fetal period, prenatal influences can affect the developing central nervous system with lifelong consequences for physical and mental health. Glucocorticoids are one of the proposed mechanisms by which fetal programing occurs. Glucocorticoids pass through the blood-brain barrier and target receptors throughout the central nervous system. Unlike endogenous glucocorticoids, synthetic glucocorticoids readily pass through the placental barrier to reach the developing fetus. The synthetic glucocorticoid, betamethasone, is routinely given prenatally to mothers at risk for preterm delivery. Over 25% of the fetuses exposed to betamethasone will be born at term. Few studies have examined the lasting consequences of antenatal treatment of betamethasone on the regulation of the hypothalamic-pituitary-adrenal (HPA) axis. The purpose of this study is to examine whether antenatal exposure to betamethasone alters circadian cortisol regulation in children who were born full term. School-aged children prenatally treated with betamethasone and born at term (n = 19, mean (SD) = 8.1 (1.2) years old) were compared to children not treated with antenatal glucocorticoids (n = 61, mean (SD) = 8.2 (1.4) years old). To measure the circadian release of cortisol, saliva samples were collected at awakening; 30, 45, and 60 min after awakening; and in the evening. Comparison children showed a typical diurnal cortisol pattern that peaked in the morning (the cortisol awakening response) and gradually decreased throughout the day. In contrast, children exposed to antenatal betamethasone lacked a cortisol awakening response and had a flatter diurnal slope (p's < 0.01). These data suggest that antenatal glucocorticoid treatment may disrupt the circadian regulation of the HPA axis among children born at term. Because disrupted circadian regulation of cortisol has been linked to mental and somatic health problems, future research is needed to determine whether children exposed to antenatal synthetic glucocorticoids are at risk for poor mental and physical health.